Determination of Glucose with Cellulose Acetate/Glucose Oxidase Modified Carbon Paste Electrodes - Rochmad Kris Sanjaya; Datin An Nisa Sukmawati; Nurul Ismillayli; Dhony Hermanto (Molekul, 2021)
An amperometric biosensor for glucose determination was developed using a carbon paste electrode (CPE) modified with cellulose acetate (CA)/glucose oxidase (GOx) bilayer membrane through the electrostatic interaction between them. The CA membrane was used as matrix for enzyme immobilization via microencapsulation technique, is enzyme placed between two membranes. CA/GOx membrane was attached to CPE surface containing ferrocene (Fc). By using proposed amperometric biosensor, glucose concentration was determined as well as its characteristic. The modified Fc–graphite electrode with CA/GOx bilayer membrane for glucose had optimum measurement conditions at work emf of 874 mV, CA concentration of 10% and amount Fc of 0.021 mg. The biosensor showed good performance at glucose concentration range of 0.05–3 mM and limit of detection was 0.024 mM. Proposed biosensor has good reproducibility with relative standard deviation (RSD) was less than 5% up to 7 times use (in the defined condition 4 ˚C). Glucose measurement result in human serum of diabetes mellitus patients showed conformity with result of reference method, MediSense Optium glucose test kit.